Draft Annual Plan 1987-88 Seventh Five Year Plan 1985-90 Statements - Planning Commission (Planning Commission, 1985)
Draft annual plan 1987-88 head of development - outlay and expenditure, draft annual plan - development schemes/project outlay expenditure, draft annual plan 1987-88-physical targets and achievements, draft annual plan 1987-88- minimum needs programme outlay and expenditure, draft annual plan 1987-88 central sector scheme/centrally sponsored scheme (outlays and expenditure), employment content of sectoral programmes 1985-90 outlay and expenditure, annual plan 1987-88 water supply & sanitation sector schemewise of urban supply / sanitation.
Government of Pondicherry Planning and Research Department Union Territory of Pondicherry